The Effect of Problem Based Learning Model on the Science Learning Outcomes Of Grade V Students of UPTD SD Negeri 122354 Pematangsiantar - Gray Zesco Brilyan Simamora; Janwar Tambunan; Bernard Simanjuntak (International Journal of Technology and Education Research, 2026)
This study was conducted based on the researcher's observation of class V of SD Negeri 122354 Pematangsiantar that teachers still use conventional learning models so that students are less involved in the learning process. This causes the learning process to be less than optimal and student learning outcomes do not meet the criteria for achieving learning objectives. From these problems, it is necessary to find a solution, including by implementing the Problem Based Learning learning model. This learning model can be applied to science subjects because it encourages students to work together and communicate with each other in completing their assignments. This learning model can improve the quality of science learning so that students are more active, creative, and learning is more meaningful so that learning outcomes increase. This study uses a quantitative method with a Pre-Experiment research type and a One Group Pretest-Posttest research design with a sample of 22 students. Based on the results of the hypothesis test with a significance level of 0.05 t count = 19.495 with a significant level (2-tailed) of 0.000 significant probability <0.05, t count> t table = 19.495> 1.717 then Ho is rejected and H1 is accepted. This explanation indicates that the Problem-Based Learning model has an influence on the science learning outcomes of fifth-grade students at the UPTD of SD Negeri 122354 Pematangsiantar.